INSTRUMEN REKOMENDASI DPRD DALAM PENYELENGGARAAN KEWENANGAN PERIJINAN OLEH PEMERINTAH DAERAH - Jayantara, Made (Jurnal Magister Hukum Udayana (Udayana Master Law Journal); Vol 4 No 3 (2015)DO - 10.24843/JMHU.2015.v04.i03.p07, 2015)
Recommendation of the Local House of Representative (DPRD) is a common administrative institution employed in the local government decision making process. However, this institution does not recognized by the law. Hence, its presence dan used in the process of decision of public license contains various problem, such as: (1) its status under the administrative law; (2) its implication to the validity of the license; (3) and the position of the head of the local government, the degree of the local government responsibility as the recommendation receiver and the DPRD as the recommendation giver to the negative impact of the license. These facts resulted in needs for conducting research for clarifying the status, measuring the implication of the recommendation over the validity of the license, and the range of responsibility head of the local government and the DPRD to the impact of the license. This research is focused into two issues, namely: (1) how is the position and function of the DPRD in the process of issuing of license; and (2) how would be the implication of the DPRD’s recommendation over the range of responsibility of the head of the local government and DPRD in the issuing of license. This research is limited to the practice of issuing of recommendation in the Local Government Province of Bali.This research shall employ normative approach and uses both primary and secondary legal resources. The research resulted in two inventions: firstly, recommendation of DPRD is not recognized by the law in the level of province local government neither it’s the authorithy of the DPRD on supervising the governor. The recommendation recognized by law is the recommendation as an administrative legal instrument in the performance of local government by the governor, particularly for performing the function of decision making or the conducting of governmental act. Hence, recommendation of DPRD is a state custom in performing state governmental function. Secondly, recommendation has two functions, namely: a condition and confirmation. In the function of condition, recommendation is a prerequisite for adopting public decision. In the function of confirmation, recommendation is a merely an expression of an agreement provided by a certain instution for adopting a public decision. Recommendation in the function of condition, binds the recommendation giver to bear responsibility over the result of the implementation of the decision. While, in the function of confirmation the giver may not necessarily responsible to the result of the performance of the decision. However, under the principle of good faith, the giver is under obligation to bear responsibility over the result of the implementation of the decision whenever the recommendation is given under a bad faith.
Keywords: legal status, function, Recommendations DPRD, Authority, Licensing